2015
DOI: 10.1136/neurintsurg-2015-011682
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion treatment of complex bifurcation aneurysms beyond the circle of Willis: a single-center series with special emphasis on covered cortical branches and perforating arteries

Abstract: Flow diversion of bifurcation aneurysms is feasible with low rates of permanent morbidity and mortality. Caliber reduction and asymptomatic occlusion of covered cortical branches seems to be common, yet ischemic complications are rather linked to perforator occlusions. Our results on aneurysm occlusion rates are preliminary and longer follow-up periods are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 25 publications
(28 reference statements)
4
60
0
5
Order By: Relevance
“…This phenomenon can be logically explained by the progressive flow reduction through the covered perforators into a brain area without adequate collateral feeders. This seems to be in line with the report by Gawlitza et al, 14 which noted that caliber reduction and asymptomatic occlusion of covered cortical branches and lacunar infarcts after FDD placement are common events, being reported in 41.2% of the procedures. No other complication occurred at the longerterm follow-up (> 24 months).…”
Section: Figsupporting
confidence: 92%
“…This phenomenon can be logically explained by the progressive flow reduction through the covered perforators into a brain area without adequate collateral feeders. This seems to be in line with the report by Gawlitza et al, 14 which noted that caliber reduction and asymptomatic occlusion of covered cortical branches and lacunar infarcts after FDD placement are common events, being reported in 41.2% of the procedures. No other complication occurred at the longerterm follow-up (> 24 months).…”
Section: Figsupporting
confidence: 92%
“…[15][16][17] In accordance with previous reports, transient symptoms were noted during the first follow-up months. 18 In our opinion, they were not related to in situ thrombotic events but rather to hemodynamic parameters. These events were not positively correlated with branch remodelling or occlusion; on the contrary, they were likely the expression of a regional decrease in perfusion, related to the presence of a moderately developed pial network, which might decrease the pressure gradient inside the jailed branch 17 but was not yet sufficient to compensate for the perfusion requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Gawlitza et al 17 found occlusion rates of just 33% after treatment of MCA and anterior communicating artery aneurysms with flow-diverter stents. The challenging factors for treating bifurcation aneurysms with flow diverters include the need to cover branch vessels and perforators with the flow-diverter stent and technical challenges with device delivery.…”
Section: Discussionmentioning
confidence: 99%